2016
DOI: 10.1039/c5ra20812b
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of ZnAl2O4nanoparticles: efficient and reusable porous nano ZnAl2O4and copper supported on ZnAl2O4catalysts for one pot green synthesis of propargylamines and imidazo[1,2-a]pyridines by A3coupling reactions

Abstract: A simple, facile and efficient route was developed for the synthesis of nano ZnAl2O4using ethanolamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 74 publications
(23 reference statements)
0
19
1
Order By: Relevance
“…The TOF obtained with the Cu-Co PBA was two orders of magnitude higher than the one obtained with Zn-Co PBA for the hydration of phenylacetylene. Contrary to previous reports 13,39 claiming that the formation of the iminium ion between the aldehyde and the amine occurs almost spontaneously above 353 K, our results show that a specific site -Zn 2+ in this case is needed for this reaction to occur considerably. Without Zn, the rapid activation of phenylacetylene (on Cu sites) yields considerable amounts of acetophenone, whereas without Cu in the structure, this activation takes place too slowly and the coupling of phenylacetylene, piperidine and benzaldehyde does not occur substantially.…”
contrasting
confidence: 99%
“…The TOF obtained with the Cu-Co PBA was two orders of magnitude higher than the one obtained with Zn-Co PBA for the hydration of phenylacetylene. Contrary to previous reports 13,39 claiming that the formation of the iminium ion between the aldehyde and the amine occurs almost spontaneously above 353 K, our results show that a specific site -Zn 2+ in this case is needed for this reaction to occur considerably. Without Zn, the rapid activation of phenylacetylene (on Cu sites) yields considerable amounts of acetophenone, whereas without Cu in the structure, this activation takes place too slowly and the coupling of phenylacetylene, piperidine and benzaldehyde does not occur substantially.…”
contrasting
confidence: 99%
“…The excellent catalytic ability of the nano porous ZnAl 2 O 4 with large surface area for the one‐pot synthesis of propargylamines via A 3 coupling of different aromatic aldehydes, piperidine and phenyl acetylene (Scheme ) was demonstrated by Sathiyanarayanan and co‐workers in 2016 . The porous nano ZnAl 2 O 4 was prepared by ethanolamine as complexing and precipitating agent between zinc nitrate and aluminium nitrate under calcinations.…”
Section: The Various Catalytic Systems For A3 Coupling Reactionsmentioning
confidence: 99%
“…It is important to stress that despite huge advancements of the reported works in the literature, another important challenges in the A 3 coupling reactions is nature of solvent and kind of the catalyst. A number of nanocatalysts, including copper, silver, gold, nickel, magnetic nanocatalysts and Co 3 O 4 , ZnS and nanopowder zinc titanate were successfully applied for A 3 coupling reactions with yields ranging from good to excellent in appropriate times in organic solvents or aqueous medium . The authors ascribed high catalytic activity of nanocatalysts to the particles size.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…14 Radical reduction through single electron transfer (SET) subsequently occurred in the presence of the indium catalyst to form intermediate (2). 39 Next, radical dehydrogenation of (2) proceeded to generate (3), which was further oxidized to afford the radial cation (5) through the formation of cyclic (4). 40 Another single electron transfer from (5) generated the indium catalyst to the catalytic cycle and provided the desired product.…”
Section: Resultsmentioning
confidence: 99%
“…Imidazo [1,2-a]pyridines are a prominent collection of biologically active nitrogen-containing heterocycles that exhibit universal applications in medicinal chemistry, agro chemistry, and materials science. [1][2][3][4][5][6] A variety of synthetic strategies, including multicomponent condensation, oxidative coupling, and tandem reaction protocols, have been developed to produce imidazo [1,2-a]pyridine derivatives with numerous substituents at the 2 and 3-positions of this moiety. [7][8][9] Gryko et al reported a productive path to a wide range of imidazo [1,2-a]pyridines via the condensation of acetophenones with 2-aminopyridines.…”
Section: Introductionmentioning
confidence: 99%